2016
DOI: 10.1108/lodj-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of leaders’ humor and employees’ work engagement mediated by positive emotions

Abstract: Purpose The purpose of this paper is to examine affective events theory (AET) by testing the mediating effect of employees’ positive affect at work in the relationships of leaders’ use of positive humor with employees’ work engagement, job performance, and organizational citizenship behaviors (OCBs); and the moderating effect of transformational leadership style on the relationship between leaders’ use of positive humor and subordinate’s positive affect at work. Design/methodology/approach Data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 64 publications
2
75
0
1
Order By: Relevance
“…For example, in Breevaart et al's (2014) study, it was found that after controlling for followers' work engagement the previous day, employees were more engaged on the following days when their leader took a more transformational leadership approach and provided contingent rewards. In addition, the leader exhibiting a sense of humor created a more pleasant and fun working atmosphere with the potential to help employees generate positive emotions at work, thereby increasing their work engagement (Goswami et al, 2016).…”
Section: The Mediating Role Of Job Satisfactionmentioning
confidence: 99%
“…For example, in Breevaart et al's (2014) study, it was found that after controlling for followers' work engagement the previous day, employees were more engaged on the following days when their leader took a more transformational leadership approach and provided contingent rewards. In addition, the leader exhibiting a sense of humor created a more pleasant and fun working atmosphere with the potential to help employees generate positive emotions at work, thereby increasing their work engagement (Goswami et al, 2016).…”
Section: The Mediating Role Of Job Satisfactionmentioning
confidence: 99%
“…In other words, if the type humor used by a leader is known, we can estimate whether or not the leader has paternalistic leadership style 35.3%. When relevant literature is reviewed, it was seen that although there are a lot of studies have focusing on various aspects of the topic such as the relationship between leadership style, the use of humor and individual and unit-level performance (Avolio et al, 1999:225), leader use of humor, transformational leadership and creative performance followers (Arendt, 2009:104;Lee, 2015:84) and transformational leadership style, leaders' positive humor and employees' positive emotions stronger (Goswami et al, 2016(Goswami et al, :1095, none of them deal with the predictive power of humor types in explaining leadership styles.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the overarching theory of our research is the affective events theory, an event-based within-person framework was used, which means our model should be tested at the individual level [29,54]. In order to avoid violating the assumption of independence in our data and to perform a multi-wave study, following the previous studies using affective events theory, we collected our samples randomly without forming the multiple subordinates nested [55,56]. Data for this study were collected from eight real estate and insurance companies in China, and participants in the survey were all front-line staff.…”
Section: Samples and Proceduresmentioning
confidence: 99%